Perihilar cholangiocarcinoma masquerading as intrahepatic cholestasis of pregnancy: a case report and review of the literature - Xiao, Chao; Cao, Cheng-Jian; Xiao, Xue; Cheng, Qi-Jun (Frontiers in Medicine, 2024)
Cholangiocarcinoma (CCA) is a tumor that arises from the epithelium of the intrahepatic bile ducts. It is rarely diagnosed in individuals under 40 years of age and has a very aggressive nature: 95% of patients die within 5 years. We present the first detailed report of a case of perihilar CCA (pCCA) presenting during pregnancy masquerading as intrahepatic cholestasis of pregnancy (ICP). First, the patient exhibited typical pruritus, particularly in her limbs; second, a raised biomarker of total bile acid (TBA) was noted; third, the onset occurred in the second trimester, aligning with the epidemiological profile; and finally, importantly, there was no mass detected in her liver. First-line drugs were given to treat ICP, but they failed, and ultimately, the condition was identified as pCCA. Following an inadequate excision, traditional Chinese medicine was administered. After 26 months, she succumbed to cachexia. As gestational symptoms are sometimes associated with pregnancy-related disorders, pCCA in pregnant women is frequently misdiagnosed. Symptoms such as jaundice, pruritus, and dilated bile ducts in pregnant women may indicate pCCA. In addition, the appropriate treatment for pCCA in pregnant women may be surgery or chemotherapy; if surgery is not an option, chemotherapy may also help extend the gestational week. Our work is important and can educate on the diagnosis and treatment of pregnancy-related diseases, such as ICP and pCCA.